Record of Animals Association with Xanthostemon novoguineensis (Valeton) - Raynard C. Sanito (Jurnal Biologi Papua, 2018)
Xanthostemon novoguineenis (vernacular name: Sowang), an endemic plant in Papua from Myrtaceae family, is found widely near the buffer zone area and Mt. Cyclops Nature Reserve (MCNR) area. This research aimed to record the association of animals towards X. novoguineensis on its natural habitat. The survey was conducted in Cyclops buffer zone near Sentani City, Papua Province, Indonesia. The result showed that an interaction of animals directly to X. novoguineensis was documented and identified. Some insects species have an association with X. novoguineensis, namely black wasp (Isodontia sp 1), black-orange wasp (Isodontia sp 2), red weaver ant (Oecophylla sp 1) and black weaver ant (Oecophylla sp 2) have an association directly to flowers of X. novoguineensis. Furthermore, stick insect (Scepthrophasma sp) and spider (possibly from Araneae family) have an association with the leaves and trunks of this plant. Based on the finding, some leaves of these plant are fed by insects. It is indicated by a pattern of insect bites on the leaves.  Key words: buffer zone area,  cyclops, insect, sowang, Papua